Relationship of adipokines (adiponectin, resistin and RBP4) with metabolic syndrome components in pubertal obese children. (June 2013) - Boyraz, Mehmet; Cekmez, Ferhat; Karaoğlu, Abdulbaki; Cinaz, Peyami; Durak, Mustafa; Bideci, Aysun
Aim: To investigate the relationship between serum adiponectin, resistin and RBP4 levels and the components of metabolic syndrome.Patients & methods: Serum adiponectin, resistin and RBP4 levels were detected and analyzed in 148 8–18-year-old Turkish obese pubertal children with/without metabolic syndrome.Results: Adiponectin and resistin concentrations were significantly inversely correlated with BMI standard deviation score, homeostatic model assessment insulin resistance, waist circumference, triglyceride levels and diastolic and systolic blood pressure, and were directly correlated with high-density lipoprotein cholesterol. RBP4 concentrations were directly correlated with homeostatic model assessment insulin resistance, waist circumference, triglyceride levels and diastolic and systolic blood pressure, and inversely correlated with high-density lipoprotein cholesterol.Conclusion: Adiponectin, RBP4 and, in particular, resistin levels may be used as suitable predictive biomarkers of metabolic syndrome.